Feasibility Study of Swallowing Assistive Gel during Capsule Swallowing in Post-Stroke Patients by Videofluoroscopic Swallowing - Meng DAI; Delian AN; Ke ZHANG; Yaowen ZHANG; Zulin DOU (康复学报)
Objective:To assess the safety and effectiveness of swallowing assistive gel (SAG) during capsule swallowing in post-stroke patients and to ascertain the clinical feasibility of SAG in managing patients'oral medication.Methods:A total of 31 post-stroke patients who were evaluated as level 4-7 in Functional OralI Intake Scale (FOIS) and showed no choking in water swallow test were recruited. Each of them would take capsules by water and SAG orally under videofluoroscopic swallowing study (VFSS). Successful swallowing ratio and quantitative parameters were evaluated and compared. We analyzed quantitative parameters included oral transit time (OTT), stage transition time (STT), pharyngeal transit time (PTT), UES opening time (UOT), delay time (DT), hyoid bone superior movement (HSM), hyoid bone anterior movement (HAM) and UES opening diameter (UOD).Results:Successful swallowing ratio was 80.65%by using SAG, which was significantly higher than 54.84%by using water (χ2=4.724, P=0.030). Oral transit time of taking capsules with SAG(3 688.2±3 370.6) ms tended to be longer (P< 0.05) than water (1 886.2±1 467.4) ms, while HSM tended to be larger (P< 0.05) by using water (15.61±5.59) mm than by using SAG(11.74±4.94) mm.Conclusion:With the advantages in lubrication and smoothness, SAG can ease capsule swallowing in post-stroke patients and bring safety as well. The method is clinically applicable.